Seroprevalence of anti-rubella and anti-measles IgG antibodies in pregnant women in Shiraz, Southern Iran: outcomes of a nationwide measles-rubella mass vaccination campaign. - Behnam Honarvar (Public Library of Science (PLoS), 2013)
Objective Nonimmune pregnant women are at risk of developing congenital rubella syndrome and measles complications. We aimed to identify pregnant women susceptible to rubella or measles in order to determine the need for immunity screening and supplemental immunization in women of childbearing age. Method This seroprevalence survey was conducted by convenience sampling in obstetric hospitals affiliated with Shiraz University of Medical Sciences (southern Iran). Serum IgG levels were measured by ELISA. Result Mean age of the 175 pregnant women was 27.3±5.3 (range 16 to 42) years. The geometric mean concentration of anti-rubella IgG was 14.9 IU/mL (CI 95%,14.1-15.5), and that of anti-measles IgG was 13.8 IU/mL (CI 95%, 13-14.5). One hundred sixty-eight women (96%) had a protective serologic level (>11 IU/mL) of IgG against rubella, and 143 (81.7%) had a protective level against measles. Except for a significant inverse correlation that was showed by univariate analysis between anti-rubella IgG and the women's age (P = 0.01), immunity did not correlate with demographic or obstetric characteristics or medical history. There was no significant correlation between anti-rubella and anti-measles IgG levels (P = 0.25). Conclusion Nearly a decade after Iran's nationwide measles-rubella vaccination campaign for the population aged 5-25 years, most pregnant women up to 34 years of age had humoral immunity against rubella. We recommend rubella immunity screening or catch-up immunization for women older than 35 years who wish to become pregnant, and measles immunity screening and appropriate vaccination for all women of childbearing age.